ANALISIS KADAR KALSIUM DAN MAGNESIUM TERHADAP KEJADIAN STUNTING BALITA DI PUSKESMAS TITIPAPAN MEDAN DELI - Ice Ratnalela Srg; Sri Bulan Nasution; Endang Sofia; Halimah Fitriani Pane (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Stunting is a growth disorder as an indicator of chronic malnutrition. One of the factors that affect stunting is the low intake of bone-forming nutrients such as calcium and magnesium which is consumed, causing the calcium content in the blood to decrease. The minerals calcium and magnesium work synergistically where magnesium helps accelerate the absorption of calcium. This study aims to analyze the difference between calcium and magnesium in stunted and non-stunted toddlers at the Titi Papan Health Center, Medan Deli District. This research was conducted in August 2020 at the Titi Papan Public Health Center, Medan Deli District, using an analytical observational research design with a cross sectional research design conducted on 35 stunted toddlers and 35 non-stunted toddlers. Sample selection using Simple Random Sampling technique. Data analysis used statistical test with T-Independent test technique. The results showed that there was a significant difference in the average calcium levels between stunted and non-stunted toddlers with a value (p=0.0001), there was no significant difference in the average magnesium levels of stunting and non-stunted toddlers with a value (p=0.176).